Improving residents' understanding of stress coping at Ar-Rahman drug rehabilitation centre - Muhamad Uyun (Universitas Muhammadiyah Magelang, 2023)
Rehabilitation is one way to overcome narcotic abuse. The entry of individuals into rehabilitation centres causes individuals to be able to adopt. However, in the field there are still many individuals who have not been able to adopt to rehabilitation centres. This program aims to develop the understanding of residents of the ar-rahman drug rehabilitation centre on stress coping. The activity consists of several stages, namely the preparation stage, the planning stage, and the implementation stage. The evaluation results showed that: 1) participants were able to understand how to react to stress; 2) have the ability to assess the situation; 3) have confidence in themselves; 4) have many ways to solve problems; 5) have the ability to adapt and make adjustments; 6) have a proactive attitude; and 7) have the ability to be able to adapt and adjust. At the end of the activity, the residents of the ar-Rahman drug rehabilitation center had an increased understanding of coping with stress.